A Positive Tropism of Rice Roots toward a Nutrient Source. (6th December 2019) - Yamazaki, Kiyoshi; Ohmori, Yoshihiro; Fujiwara, Toru
Abstract: Plants take up water and nutrients through roots, and uptake efficiency depends on root behavior. Roots recognize the moisture gradient in the soil and grow toward the direction of high moisture. This phenomenon is called hydrotropism, and it contributes to efficient water uptake. As nutrients in soil are also unevenly distributed, it is beneficial for plants to grow their roots in the direction of increasing nutrient concentrations, but such a phenomenon has not been demonstrated. Here, we describe the directional growth of roots in response to a nutrient gradient. Using our assay system, the gradient of a nitrogen nutrient, NH 4 +, was sufficient to stimulate positive tropic responses of rice lateral roots. This phenomenon is a tropism of plant roots to nutrients; hence, we propose the name 'nutritropism'. As well as other tropisms, differential cell elongation was observed before the elongation zone during nutritropism, but the pattern promoting cell elongation preferentially on the non-stimulated side was opposite to those in root hydrotropism and gravitropism. Our evaluation of the NH 4 + gradient suggested that the root tips responded to a sub-micromolar difference in NH 4 + concentration on both sides of the root. Hydrotropism, gravitropism and phototropism were described in plants as the 'power of movement' by Charles and Francis Darwin in 1880, and these three tropisms have attracted the attention of plant scientists for more than 130 years. Our discovery of nutritropism represents the fourth 'power of movement' in plants and provides a novel root behavioral property used by plants to acquire nutrients efficiently.